Fair and foul beyond the myths and paradoxes of sport - Eitzen, D. Stanley (ROWMAN & LITTLEFIELD, 2016)
Fair and Foul explores our loves of sport, just as it reveals sport's darker side-the influence of big business, corruption, price gouging, political maneuvering, gender bias, media control, and more. The sixth edition features a new chapter on mass media and sport, a revised chapter on college sport that asks whether big-time college sports are compatible with higher education. This edition also features new material throughout, such as the rising costs and increasing injuries in youth sports, fantasy sports, homophobia in sport, "one and done", and more. Fair and Foul draws on examples ranging from youth to pro sports to give us a deeper understanding of how to shape our everyday world. Ideal for sparking classroom discussion, Fair and Foul is an excellent book for students of sports and society, American culture, and other courses